CONCEPT OF EVALUATION OF CREDITWORTHINESS OF ENTERPRISES IN CONDITIONS OF ECONOMIC CYCLE - USYK, Vladislava (Theoretical and Practical Research in Economic Fields; Vol 11 No 2 (2020): TPREF, Volume XI, Issue 2(22), Winter 2020, 2020)
The economic content and components of creditworthiness of enterprises are substantiated. An in-depth critical analysis and structuring of the main tools and methods for assessing the creditworthiness of enterprises in the current conditions of transformation of the world market. The classification of the main factors influencing the formation of creditworthiness of enterprises and should be taken into account in the formation of strategic guidelines for each enterprise is proposed. The main criteria for assessing the creditworthiness of enterprises depending on the type and specificity of economic activity based on the analysis of credit risk models are substantiated. The concept of assessing the creditworthiness of enterprises in modern conditions of economic cyclicality, taking into account the characteristics of the industry, volume and specifics of activities. A method of assessing the creditworthiness of enterprises by type of economic activity using multidimensional discriminant analysis taking into account the influence of various factors, both internal and external environment, which, unlike existing ones, will quickly determine the financial condition and determine and take into account the impact of various factors. The developed concept of assessing the creditworthiness of enterprises through multidimensional discriminant analysis will ensure effective management decisions and optimize the financial condition.